2013
DOI: 10.1134/s0006297913010033
|View full text |Cite
|
Sign up to set email alerts
|

Keap1/Nrf2/ARE redox-sensitive signaling system as a pharmacological target

Abstract: The redox-sensitive signaling system Keap1/Nrf2/ARE plays a key role in maintenance of cellular homeostasis under stress, inflammatory, carcinogenic, and proapoptotic conditions, which allows us to consider it as a pharmacological target. Here we review the basic regulatory mechanisms of the Keap1/Nrf2/ARE system, key targets for pharmacological intervention, and interconnection of this system with other redox-sensitive transcriptional factors. We also discuss the range of currently available pharmaceuticals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 155 publications
0
47
0
1
Order By: Relevance
“…However, these plant extracts have a very wide range of biological effects, making it difficult to distinguish the true contribution of Nrf2 induction. Currently, more specific and effective synthetic chemicals are being developed [11]. In this study we report that lansoprazole is a strong and effective inducer of Nrf2 transcription in hepatocytes, in addition to acting as a proton pump inhibitor.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, these plant extracts have a very wide range of biological effects, making it difficult to distinguish the true contribution of Nrf2 induction. Currently, more specific and effective synthetic chemicals are being developed [11]. In this study we report that lansoprazole is a strong and effective inducer of Nrf2 transcription in hepatocytes, in addition to acting as a proton pump inhibitor.…”
Section: Introductionmentioning
confidence: 76%
“…Nrf2 is a master transcription factor that regulates antioxidant response element (ARE)-mediated transcription of genes involved in the regulation of the synthesis and conjugation of glutathione (glutamate-cysteine ligase catalytic subunit), antioxidant proteins specializing in the detoxification of certain reactive species (HO-1), drug-metabolizing enzymes (UDP-glucuronosyl-transferase 1A1), xenobiotic transporters (multidrug resistance protein 1), and molecular chaperones [9][11]. Nrf2 is sequestered in the cytoplasm by Kelch-like ECH-associated protein (Keap1) under un-stimulated conditions, while Nrf2 is translocated into the nucleus and activates the electrophilic response element/antioxidant response element (EpRE/ARE) upon exposure to oxidative insults [9][11]. It was shown that significant amounts of the Nrf2-Keap1 complex remained in the bound form after exposure to electrophiles [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Upon inflammation response, cells maintain redox homeostasis by regulating oxidative stress by induction of phase II antioxidant enzymes such as heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase-1 (NQO-1), and c-glutamylcysteine synthase (c-GCLC) is regulated by the nuclear factor erythroid 2-related factor-2 (Nrf2) signaling [25][26][27]. The activation of Nrf2 signaling induces the translocation of Nrf2 into the nucleus and mediates the its transcriptional activity, resulting in the increased expression of antioxidant enzymes that play important roles in scavenging free radicals, such as superoxide dismutase (SOD) and catalase (CAT) [28]. Therefore, Nrf2 signaling and its related activities are critically involved in the NF-jB-dependent inflammation response.…”
Section: Introductionmentioning
confidence: 99%
“…Inactive NRF2 is retained in the cytoplasm by association with the kelch-like ECH-associated protein 1 (KEAP1), but during inflammation or oxidative stress, the phosphorylation of some intracellular kinases, such as phosphoinositide 3-kinase (PI3K) and protein kinase B (AKT), elicits the translocation of NRF2 to the nucleus. Then, NRF2 binds to the antioxidant response elements (ARE) within the promoter of antioxidant enzymes, activating their transcription [10]. The most relevant of these enzymes are heme oxygenase-1 (HO1), nicotinamide adenine dinucleotide phosphate dehydrogenase quinone 1 (NQO1), superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) [11].…”
Section: Introductionmentioning
confidence: 99%